An Analysis of Figurative Possession in the Film Golden Compass - Azizah, Khoirotul; Wibowo, Joko (International Journal on Advanced Science, Education, and Religion, 2025)
In the era of globalization and technological advancement, films have become a popular medium accessible to all groups, serving not only as entertainment but also as carriers of social, cultural, psychological, and linguistic values. Figurative language in films plays a crucial role in enriching narratives and expressing abstract ideas through more concrete and imaginative forms. This study focuses on analyzing figurative sentences containing possessive meaning in the film The Golden Compass using a qualitative descriptive approach. The data, taken from character dialogues, were identified, classified, and analyzed to reveal the possessive meanings embedded in them. The findings show five figurative sentences with possessive meaning that significantly contribute to strengthening characterization, portraying emotional bonds, and representing power relations among the characters. These results indicate that figurative language functions not only as an aesthetic device but also as a means of psychological and social representation. Theoretically, this research broadens insights into linguistic studies, while practically it can be applied as learning material in language and literature education to foster appreciation of figurative language in real contexts. Thus, films can be regarded as both a medium of learning and a reflection of life values.